Oncogenic Viruses-Encoded microRNAs and Their Role in the Progression of Cancer: Emerging Targets for Antiviral and Anticancer Therapies - Mahmoud Kandeel (MDPI AG, 2023)
Approximately 20% of all cases of human cancer are caused by viral infections. Although a great number of viruses are capable of causing a wide range of tumors in animals, only seven of these viruses have been linked to human malignancies and are presently classified as oncogenic viruses. These include the Epstein-Barr virus (EBV), human papillomavirus (HPV), hepatitis B virus (HBV), hepatitis C virus (HCV), Merkel cell polyomavirus (MCPyV), human herpesvirus 8 (HHV8), and human T-cell lymphotropic virus type 1 (HTLV-1). Some other viruses, such as the human immunodeficiency virus (HIV), are associated with highly oncogenic activities. It is possible that virally encoded microRNAs (miRNAs), which are ideal non-immunogenic tools for viruses, play a significant role in carcinogenic processes. Both virus-derived microRNAs (v-miRNAs) and host-derived microRNAs (host miRNAs) can influence the expression of various host-derived and virus-derived genes. The current literature review begins with an explanation of how viral infections might exert their oncogenic properties in human neoplasms, and then goes on to discuss the impact of diverse viral infections on the advancement of several types of malignancies via the expression of v-miRNAs. Finally, the role of new anti-oncoviral therapies that could target these neoplasms is discussed.